2011
DOI: 10.1074/jbc.m111.306951
|View full text |Cite
|
Sign up to set email alerts
|

An Environment-dependent Structural Switch Underlies the Regulation of Carnitine Palmitoyltransferase 1A

Abstract: Background:The enzyme carnitine palmitoyltransferase 1 regulates the rate of fatty acid oxidation. Results: The regulatory domain of the enzyme constitutes an amphiphilic structural switch. Conclusion:The switch can integrate enzyme inhibitor concentration and membrane characteristics into one regulatory signal. Significance: This represents a highly sophisticated regulatory mechanism for enzymes residing at the membrane-water interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 65 publications
1
50
0
Order By: Relevance
“…20 Gene expression, 2 H/ 13 C/ 15 N labeling, and purification of the N domain (Arg37Cys) were carried out as described for the wild-type N domain elsewhere. 21 Two samples, Nα and Nβ, which corresponded to an inhibitory and noninhibitory state in CPT1A, were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…20 Gene expression, 2 H/ 13 C/ 15 N labeling, and purification of the N domain (Arg37Cys) were carried out as described for the wild-type N domain elsewhere. 21 Two samples, Nα and Nβ, which corresponded to an inhibitory and noninhibitory state in CPT1A, were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…The authors performed the experiments under the same conditions as those used in a previous study on the three-dimensional structure of the CPT1A N-terminal domain [15]. They observed that the CPT1C N-terminal domain adopted an inhibitory Nα state that structurally matches that observed for CPT1A.…”
Section: Spatial Structure Of the N-terminal Domainmentioning
confidence: 99%
“…In addition, changes in the malonyl-CoA sensitivity of the enzyme have also been associated with homo-oligomerization [16,17] or heteroassociation with other proteins [18], and they also depend on the composition and curvature of the membrane in which CPT1A lies [15,19].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Physical changes to OMM properties due to loss of an abundant protein. There is evidence that the fatty acid transport protein CPT1A activity could be regulated by changes in OMM lipid composition and molecular order (Rao et al 2011). Irrespective of the precise mechanism, a function for TSPO in fatty acid metabolism could explain its abundant presence in cells that are active in lipid storage.…”
Section: Tspo As a Regulator Of Lipid Metabolismmentioning
confidence: 99%